2009
DOI: 10.1096/fj.08-126417
|View full text |Cite
|
Sign up to set email alerts
|

Thyrotropin releasing hormone (TRH): a new player in human hair‐growth control

Abstract: Thyrotropin-releasing hormone (TRH) is the most proximal component of the hypothalamic-pituitary-thyroid axis that regulates thyroid hormone synthesis. Since transcripts for members of this axis were detected in cultured normal human skin cells and since human hair follicles (HFs) respond to stimulation with thyrotropin, we now have studied whether human HF functions are also modulated by TRH. Here we report that the epithelium of normal human scalp HFs expresses not only TRH receptors (TRH-R) but also TRH its… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

1
56
0

Year Published

2011
2011
2024
2024

Publication Types

Select...
3
2
2

Relationship

2
5

Authors

Journals

citations
Cited by 71 publications
(64 citation statements)
references
References 53 publications
(54 reference statements)
1
56
0
Order By: Relevance
“…The main consequence of this connection is the stimulation of secretion of thyroid-stimulating hormone. In response, the thyroid-stimulating hormone stimulates the release of thyroxine, which is important in developing skeletal muscle of vertebrates (Larsson et al 1994;Gáspár et al 2010). The study by Liu et al (2009) is pointed by the catalog of the National Human Genome Research Institute (Hindorff et al 2010) as the only work that found the association of TRHR gene and body mass (lean).…”
Section: Discussionmentioning
confidence: 99%
“…The main consequence of this connection is the stimulation of secretion of thyroid-stimulating hormone. In response, the thyroid-stimulating hormone stimulates the release of thyroxine, which is important in developing skeletal muscle of vertebrates (Larsson et al 1994;Gáspár et al 2010). The study by Liu et al (2009) is pointed by the catalog of the National Human Genome Research Institute (Hindorff et al 2010) as the only work that found the association of TRHR gene and body mass (lean).…”
Section: Discussionmentioning
confidence: 99%
“…Therefore, we have asked whether TSH operates as a novel neuroendocrine regulator of human keratins in situ, using microdissected, organ-cultured human scalp HFs as a physiologically and clinically relevant assay systems [3][4][5]. This was complemented by studying the effect of TSH on keratin expression in cultured human outer root sheath (ORS) keratinocytes (KCs).Anagen VI HFs were isolated from normal frontotemporal scalp skin obtained after written informed consent from three healthy females undergoing routine face-lift surgery, as 3 previously described [4,5], adhering to Helsinki guidelines and under a licence from the ethics committee of the University of Lübeck. HF mRNA extracts from one female patient were subjected to quantitative real time PCR (qPCR) for selected hair keratin genes after 24 hrs treatment with TSH (100 mU ml -1 ) or vehicle.…”
mentioning
confidence: 99%
“…The importance of the latter is highlighted by the recent discovery that the "pituitary" neuropeptide hormone, prolactin, which is also expressed by human HFs, potently regulates the expression of selected human keratins on the gene and protein level [3]. Moreover, microarray analyses had provided first clues that thyroid stimulating hormone (TSH) and its proximal regulator in the hypothalamic-pituitary-thyroid axis, thyrotropin-releasing hormone (TRH), might operate as previously unsuspected modulators of human hair keratin and KAP gene transcription in situ [4][5][6]. Also, we had recently found that TSH upregulates keratin K5 gene expression and protein synthesis as well as K14 transcription in human epidermis [4].…”
mentioning
confidence: 99%
See 2 more Smart Citations